Matriks, Model, dan Varian Dalam Lagu Pretender Karya Hige Dandism: Kajian Semiotika Riffaterre: Matrix, Model, and Variants in The Song Pretender by Hige Dandism: A Study of Riiffaterre's Semiotics - Erika Selphie Damayanti; Parastuti; Prasetyo, Joko (Undiksha Press, 2025)
The determination of matrices, models, and variants of a song called Pretender is intended to describe the meaning of the song. The theory used refers to the semiotics model of Michael Riffaterre. In this study, the method used is a qualitative-descriptive, non-interactive research approach, see notes, and literature studies. Based on the results and discussion, matrices, models, and variants in Riffaterre's semiotics can clarify the subject matter that the songwriter wants to convey through the lyrics. The variants that are the subject matter are broken down through 5 arrays. The matrix or keyword in the song Pretender by HIGE DANdism reads